Employee Presence Application System Using Android-Based Qr Code Reader - Muhammad Syahputra Novelan; Aminuddin Indra Permana (Institute of Computer Science (IOCS), 2022)
At this time there are still many companies or government offices that still use manual attendance, especially in the office of the head of the village of kelambir 5, sub-district of expanse of silver, deli, serdang district. The office is utilized by technology that is currently widely used by the public, namely by using gang devices such as smartphones. So with manual systems such as signatures on paper, it is caused by frequent manipulation of attendance data. The manual attendance system can also cause the village head office administration to manually collect attendance data in large quantities, and the process becomes ineffective and inefficient. Therefore, it is necessary to have a system designed, namely an employee attendance application system using an Android-based QR Code Reader. So with the system that will be made, employee attendance data is automatically stored into the website database and it is easy to recapitulate attendance. For processing databases on the website using Mysql and making websites using the PHP programming language, then making android applications using Android Studio